WAVE : a virtual audio environment: an immersive musical instrument using a low cost technological system - Valbom, Leonel (2004)
The WAVE project proposes a multidisciplinary investigation in order to create a model-prototype of a virtual immersive instrument using audio, visual technologies, and virtual reality. This model will open up new horizons for the processes involved in music making by dealing not only with relevant technological issues, but especially with meaningful research in theareas of human-machine interaction and sound.